The epidemiology of surgically treated acute subdural and epidural hematomas in patients with head injuries: a population-based study - Tallon, John M., MD; Ackroyd-Stolarz, Stacy, PhD; Karim, Saleema A., MHSA, MBA; Clarke, David B., MDCM, PhD (Canadian Journal of Surgery, 2008)
Background The purpose of this paper is to review the population-based epidemiology of surgically treated post-traumatic epidural hematomas (EDHs) and/or subdural hematomas (SDHs) among patients who presented to the single neurosurgical centre in Nova Scotia. Methods We included all patients aged 16 years or older who presented to the tertiary care hospital with acute post-traumatic EDHs and/or SDHs between May 23, 1996, and May 22, 2005, and who were surgically treated. We generated an initial cohort from the provincial trauma registry and reviewed a total of 152 charts for possible inclusion; 70 (46%) patients met the study criteria. We performed a blinded, explicit chart review using a standardized data collection form, and we generated descriptive statistics. Results Of the patients who had surgery, 34 (49%) presented with SDHs, 23 (33%) presented with EDHs and 13 (19%) presented with both conditions. The median age was 45 years, and 80% of the cohort was male. The major mechanisms of injury were falls (51%), motor vehicle collisions (30%) and assault (11%). More than half (61%) of patients were transferred from referring hospitals while the remainder (39%) arrived directly without an intermediate facility. There were 18 postoperative deaths (26%). Forty-four of 70 patients (63%) had associated good outcomes at 6 months (Glasgow Outcome Scale). Conclusion Acute post-traumatic EDHs and/or SDHs are relatively rare (0.83/100 000 population per annum) and are generally associated with good outcomes. Death was more likely among older, more severely injured patients and among those who required surgery for SDH rather than EDH.